A Framework for Unambiguous and Extensible Specification of DSMLs for Cyber-Physical Systems - Simko, Gabor; Lindecker, David; Levendovszky, Tihamer; Jackson, Ethan; Neema, Sandeep; Sztipanovits, Janos (2013 20th IEEE International Conference and Workshops on the Engineering of Computer Based Systems (ECBS), 2013)
Increased emphasis on developing model-based design methods for Cyber-Physical Systems (CPS) brings new challenges to the specification of domain specific modeling languages (DSML) and the integration of heterogeneous CPS components.Since CPS are composed of tightly integrated physical and computational components, the modeled domains include both physical and computational systems.Formal specification of physical and computational languages as well as their integration remains an interesting challenge.In this paper we introduce a formal logic based framework for formal specification and simulation, that is supported by the fixed-point logic language FORMULA.As a representative case study, we define both the structural and behavioral semantics for a bond graph language, and demonstrate the reusability and extensibility provided by the approach by extending the language to support hybrid dynamics.